Disaster Supply Chain Management: Responsive Inter-organizational Networks Under Pressure - Stavros T. Ponis; Epaminondas Koronis (International Journal of Supply Chain Management, 2017)
Supply Chains are often required to absorb unexpected pressure, turbulent changes in demand and disruptions across their structural components. In this paper, we acknowledge both the inter-organizational and collaborative nature of supply chains and explore how established logistics structures respond to conditions of crises as a result of unforeseen natural events and disasters. After a brief review of existing practices in the area of Disaster Supply Chain Management (DCSM) we focus on identifying and presenting the sharing 'realities' of inter-organizational networks through a short case study showcasing the situational, complex and temporal nature of responsive networks under pressure.